Effect of planting method and soil texture on the growth and development of Arachis pintoi - Baruch, Z; Fisher, Myles J. (1996)
Arachis pintoi is a valuable forage legume for tropical savannas, persisting with vigorous tropical grasses under widely differing management systems. However, seed is expensive, so that vegetative planting is an option, particularly for small farmers. We studied the growth and development of A. pintoi cv. Mani Forrajero (CIAT 17434) planted from seed (S-plants) and cuttings (C-plants) on a sandy and a clay soil in cylinders in a greenhouse. Yield of above- and below-ground plant parts, leaf area and root length were measured in 10 harvests spread over 99 days. S-plants had higher total; leaf and root yields and lower shoot: root ratios than C-plants. Root growth of S-plants was deeper and faster than that of C-plants, which had shallower and more diffuse roots. Soil texture had only small effects. Although S-plants appear to have more desirable characteristics for field establishment, the effect of competition when sown into established grass swards may be more important. Moreover, practical and economic considerations may be more important than agronomic superiority in dictating farmers' choices.